(untitled) (Praxis Educativa, 2025)
The present contribution aims at analyzing community education practices related to forestry use in the San Jeronimo Coatlan rural nucleus, state of Oaxaca, in the south of México. This is about education processes outside school settings, which implies that the education agents, times and spaces are determined according to community dynamics. This is an ethnographic study, with historical perspective, retrieving camp data which were gathered during the forestry use cycle going from February to August 2024. The main findings show that since the community entered the forest market, in the 1970 decade, there has been a continuous intergenerational transmission of knowledge, which nowadays allows them to have autonomy in the forestry and territory use. Also, a variety of internal negotiations processes, including tensions and agreements, were observed. A third finding is related to technical forest learning, that is, related to the way of working during wood extraction. Finally, it was observed that, based on these processes, the community in question has built strategies for autoregulation in the forest and wood resources management. The conclusion is that there exists a process to build education and forestry autonomy aiming at the preservation of the forest as a place that allows economic and social sustenance of the community.